Valores de Creatinina y Microalbuminuria como indicadores de enfermedad Renal en personas Diabéticas que acuden al Área de Salud N° 2 Hugo Guillermo González. - Pambi Correa, Evelyn Jackeline (2013)
Nephropathy is a major cause of illness and death in people with diabetes. Is a disease of the kidney, including inflammatory processes related degenerative sclerotic persistent hyperglycemia associated with other factors (hypertension, dyslipidemia, genetic predisposition). In the province of Loja , was recorded 1145 Diabetics who came to receive care each year according to the National Institute of Statistics and Census ( INEC ) in 2011 , and about 780 people are served by some form of kidney disease. Knowing this public health problem arises the initiative to contribute to the resolution and prevention of diabetic nephropathy , which was carried by the cross-sectional study with the objective of determining creatinine in serum kinetic colorimetric method ( color reaction ) and semiquantitative microalbuminuria immunological diabetics attending the Health Area No. 2 " Guillermo González Hugo " and compared with basal glucose values ​​determined by enzymatic colorimetric test ( color reaction ) . Drawing shows 42 people who met the inclusion criteria, with the following results: the population was female predominant with 76.19 %. Basal glucose tests showed high values ​​in 76.19 %, with elevated creatinine at 21.43 % and microalbuminuria was found with 50mg / l at 11.90%, and with 100 mg / l in 9.52 %. By linking clinical analysis we can conclude that 21.43 %, basal blood glucose levels present, elevated creatinine and microalbuminuria positive, demonstrating that these individuals had evidence of diabetic nephropathy. Keywords: nephropathy, Diabetes, Creatinine, Microalbuminuria, Baseline glycemia .